1976
DOI: 10.1038/260495a0
|View full text |Cite
|
Sign up to set email alerts
|

Genomic transcriptional activity and the structure of chromatin

Abstract: Nucleic acid hybridisation has shown that micrococcal nuclease-derived chromatin subunits from the cells of Xenopus laevis contain fragments of ribosomal 28S, 18S and 5S RNAS within the population of 200 base-pair pieces of DNA. Subunits from cultured embryonic cells actively transcribing ribosomal RNA contain only 70-74% of the cistrons present in undigested wild-type DNA, while subunits from adult erythrocytes not active in RNA transcription contain close to 90% of the ribosomal cistrons in native chromatin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
39
2

Year Published

1978
1978
2014
2014

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(44 citation statements)
references
References 40 publications
3
39
2
Order By: Relevance
“…Micrococcal nuclease digestion patterns ofX. laevis ribosomal chromatin in different cell types have always been consistent with the presence of a considerable fraction of nucleosomes in the coding regions (38,39,46), which in the light of our results can be interpreted as being released from the transcriptionally inactive sequences present within the mixed population.…”
Section: Resultsmentioning
confidence: 56%
“…Micrococcal nuclease digestion patterns ofX. laevis ribosomal chromatin in different cell types have always been consistent with the presence of a considerable fraction of nucleosomes in the coding regions (38,39,46), which in the light of our results can be interpreted as being released from the transcriptionally inactive sequences present within the mixed population.…”
Section: Resultsmentioning
confidence: 56%
“…The findings in various laboratories that transcriptional complexes and/or sequences complementary to transcriptional products can be recovered in the nucleosomal fraction obtained by nuclease digestions (for example, Lacy and Axel , 1975;Gottesfeld et al ., 1975;Garel and Axel, 1976;Mathis and Gorovsky , 1976;Kuo et aI. , 1976;Piper et aI., 1976;Reeves and Jones, 1976;Reeves, 1976Reeves, , 1977Brown et al ., 1977) are not contrad ictory to the conclusion that nucleosomal beads are absent in chromatin regions engaged in transcription. It has been shown that nucleosome-sized fragments are also obtained from digestion with micrococcal nuclease when chromatin is unfolded as , for example, in high urea concentrations (Jackson and Ghalkley, 1975; for related observations, see also Woodcock and Frado, 1977;Oudet, Spadafora, and Ghambon, 1977) .…”
Section: Discussionmentioning
confidence: 99%
“…However, with the advent of massively parallel short-read DNA sequencing and its potential for single base-pair resolution, there has been a renaissance of interest in traditional methods for chromatin characterization, including the use of bisulfite sequencing for mapping DNA methylation [10] and the use of non-specific nucleases, including micrococcal nuclease (MNase) [11], deoxyribonuclease I (DNase I) [12] and exonuclease [13] (Table 1). Here, we focus on recently developed strategies for characterizing nucleosomes, TFs and chromatin-associated proteins at base-pair resolution, and we discuss prospects for full epigenome characterization.…”
Section: The Epigenomementioning
confidence: 99%